Análisis comparativo de las uniones de hecho en las legislaciones latinoamericanas - Jiménez Castillo, Selena del Cisne (2023)
The present Curricular Integration Project and Legal Research, titled: "Comparative Analysis of Common-Law Unions in Latin American Legislations," is of particular interest, as it delves into the distinct concepts and prerequisites for the formation of common-law unions within various Latin American legislations. The study has generated significant debate in certain Latin American countries in recent years. Consequently, the author has identified the necessity to analyze fourteen Latin American legislations to elucidate and acknowledge the similarities and differences between those laws and the legislation in Ecuador. This is attributed to the growing trend of couples opting for cohabitation, commonly known as common-law unions, instead of traditional marriage. The significance of conducting this research lies in the opportunity to analyze and compare common-law unions in Latin American legislations, thereby acquiring new insights regarding the legal certainty surrounding such unions within the legislations. In the context of Ecuador, the Constitution of the Republic, specifically in Article 67, acknowledges the family in its diverse manifestations. The responsibility of safeguarding the family as the fundamental cornerstone of society rests upon the Ecuadorian State and its institutions. Consequently, it becomes imperative to analyze aspects pertaining to common-law unions, considering their historical significance as one of the primitive forms through which human beings established relationships, pre-dating the formal legal institution of marriage. Thus, there arises the necessity to analyze, through comparative law, the legal situations inherent to common-law unions. This includes aspects such as the presumed duration of their establishment, necessary requirements for recognition, the entities or individuals empowered to declare and register such unions, legal implications on civil status, impediments, communal property, alternative economic frameworks, and above all, the rights and obligations entailed within this legal institution. In the present curricular integration project, various materials and methods were employed to facilitate the research process. Interviews and surveys were conducted with legal professionals, specifically in the field of Civil Law, yielding results that proved instrumental in gathering essential information for addressing the central issue at hand.